2014
DOI: 10.1073/pnas.1418629112
|View full text |Cite
|
Sign up to set email alerts
|

Gas1 is a receptor for sonic hedgehog to repel enteric axons

Abstract: The myenteric plexus of the enteric nervous system controls the movement of smooth muscles in the gastrointestinal system. They extend their axons between two peripheral smooth muscle layers to form a tubular meshwork arborizing the gut wall. How a tubular axonal meshwork becomes established without invading centrally toward the gut epithelium has not been addressed. We provide evidence here that sonic hedgehog (Shh) secreted from the gut epithelium prevents central projections of enteric axons, thereby forcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 47 publications
2
43
0
Order By: Relevance
“…In Shh −/− mice, the intestine contains increased numbers of neurons that differentiate ectopically under the epithelium and project abnormal extensions into the villi (Ramalho-Santos et al, 2000; Jin et al, 2015). Deletion of Gas1, a Hh cell-surface receptor, or Gnaz, an intracellular effector for Gas1, leads to similar phenotypes, with mislocalized enteric ganglia and increased enteric neuronal numbers (Biau et al, 2013;Jin et al, 2015). Conversely, overexpression of Gli1 leads to a patchy absence of enteric ganglia in the gut (Yang et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In Shh −/− mice, the intestine contains increased numbers of neurons that differentiate ectopically under the epithelium and project abnormal extensions into the villi (Ramalho-Santos et al, 2000; Jin et al, 2015). Deletion of Gas1, a Hh cell-surface receptor, or Gnaz, an intracellular effector for Gas1, leads to similar phenotypes, with mislocalized enteric ganglia and increased enteric neuronal numbers (Biau et al, 2013;Jin et al, 2015). Conversely, overexpression of Gli1 leads to a patchy absence of enteric ganglia in the gut (Yang et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Recent sequencing of DNA and genome-wide association studies identified mutations in Ptc1 and Gli genes in human HSCR [170,171]. In Shh -deficient mice, ENCCs colonize the gut but develop ectopic ganglia in the subepithelial mesenchyme, increased neuronal cell numbers, and abnormal neurite projections [172,173]. Inhibiting SHH signaling using cyclopamine or function-blocking antibody resulted in similar large, ectopic ganglia adjacent to the epithelium, while SHH overexpression led to intestinal aganglionosis [148].…”
Section: Molecular and Cellular Control Of Ens Developmentmentioning
confidence: 99%
“…In addition, components of the Shh signaling pathway can also regulate transcription-independent cellular processes. This nontranscriptional branch of the pathway regulates axon guidance (Charron et al ., 2003; Sánchez-Camacho and Bovolenta, 2008; Jin et al ., 2015) and fibroblast migration (Bijlsma et al ., 2007, 2012). Of note, Shh-dependent chemotaxis in fibroblasts occurs even in cells completely lacking cilia, suggesting that nontranscriptional Shh signaling is cilia-independent (Bijlsma et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%